2019
DOI: 10.1159/000498834
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the Lipid Profile and Renal Dysfunction in the Heart Failure Patients

Abstract: Background/Aims: In heart failure patients with high prevalence of chronic renal disease (CKD), hospitalization and mortality, whether the lipid profile was associated with renal dysfunction remained unknown. The present study intended to clarify the association between the lipid profile and renal dysfunction in the heart failure patients. Methods: 336 hospitalized heart failure patients with left ventricle ejection fraction (LVEF) ≤45% and New York Heart Association (NYHA) class II-IV were enrolled. The estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 51 publications
2
14
0
Order By: Relevance
“…The results of the present study are in agreement with the majority of literature, yet, in many studies, the direct and independent relationship between higher levels of lipids with the progression of kidney diseases was missing [41]. The relation between HDL-C with kidney dysfunction is presented in many studies, yet, the topic remains controversial whether it can be used as an indicator for predicting renal dysfunctions [42]. In a previous study, lipid dyslipidemia in kidney disease patients is linked to high TG levels, normal or slightly low LDL-C, and decreased HDL-C levels [43].…”
Section: Discussionsupporting
confidence: 88%
“…The results of the present study are in agreement with the majority of literature, yet, in many studies, the direct and independent relationship between higher levels of lipids with the progression of kidney diseases was missing [41]. The relation between HDL-C with kidney dysfunction is presented in many studies, yet, the topic remains controversial whether it can be used as an indicator for predicting renal dysfunctions [42]. In a previous study, lipid dyslipidemia in kidney disease patients is linked to high TG levels, normal or slightly low LDL-C, and decreased HDL-C levels [43].…”
Section: Discussionsupporting
confidence: 88%
“…change in odds of 1.5). This is consistent with literature that shows a link between chronic kidney disease with heart failure, and with hyperlipidaemia, respectively [24,25]. Pathophysiological features indicate that heart failure can cause a reduction in cardiac output and decrease in renal perfusion which are primary drivers of renal dysfunction in heart failure.…”
Section: Quantifying Disease Interactionssupporting
confidence: 92%
“…Zhang et al have demonstrated no association between TC, TG, LDL-C, and Apolipoprotein B with eGFR in patients with CKD. Only HDL-C was significantly positively associated with renal dysfunction [ 50 ]. Seok-Hyung Kim et al detected Apolipoprotein B/A1 ratio’s predictive ability for coronary artery calcification only in patients with normal kidney function [ 51 ].…”
Section: Discussionmentioning
confidence: 99%